Effect of physiochemical parameters on yield and biological efficiency of Volvariella volvacea cultivated on empty fruit bunch pellets - Amir, Nur Fariha; Mohd-Aris, Aslizah; Tuan-Zakaria, Tuan Norhafizah; Umor, Noor Azrimi; Mohamad, Azhar; Mohd Razali, Nornadiah; Mohd Yusof, Farida Zuraina; Abdullah, Sumaiyah (Elsevier, 2025)
Background: Volvariella volvacea is a highly nutritious edible mushroom grown mainly in Southeast Asian countries. However, the low yield of V. volvacea has discouraged farmers from engaging in its production. Objective: The study was conducted to observe the improvement of V. volvacea yield depending on various physiochemical parameters of V. volvacea growth. Methods: The parameters tested in this study include the weight of the substrate, i.e., 2 kg (W1) and 6 kg (W2); the surface area of the substrate: A1 (1218 cm2), A2 (1530 cm2) and A3 (2000 cm2); and four different substrate formulations (F1, F2, F3 and F4). Results: Substrate weight and surface area were found to be important, but not critical, factors in determining fruiting bodies formation, total fungal mass, and BE rate. However, the formulation media showed a significant contribution that could help in the induction of fruiting bodies. According to the results, the culture medium with a mixture of EFB substrate and black soil showed the highest BE percentage of 17.75 % (at optimised substrate weights = 2 kg). Conclusion: The results of this study can be used as a reference for further studies to improve the cultivation of V. volvacea, especially when EFB fibres are used as the main substrate. Future studies to identify genes involved in the formation of fruiting bodies are strongly recommended.